Designing user interfaces for an aging population : towards universal design - Johnson, Jeff, 1941-; Finn, Kate (Morgan Kaufmann Publishers, 2017)
Designing User Interfaces for an Aging Population: Towards Universal Design presents age-friendly design guidelines that are well-established, agreed-upon, research-based, actionable, and applicable across a variety of modern technology platforms. The book offers guidance for product engineers, designers, or students who want to produce technological products and online services that can be easily and successfully used by older adults and other populations. It presents typical age-related characteristics, addressing vision and visual design, hand-eye coordination and ergonomics, hearing and sound, speech and comprehension, navigation, focus, cognition, attention, learning, memory, content and writing, attitude and affect, and general accessibility. The authors explore characteristics of aging via realistic personas which demonstrate the impact of design decisions on actual users over age 55.